Pengaruh Booklet Stimulasi Intervensi Pertumbuhan Dan Perkembangan Pada Bayi Prematur Terhadap Peningkatan Pertumbuhan Dan Perkembangan Bayi - Rosalinna Rosalinna; Asti Andriyani (Jurnal Kebidanan dan Kesehatan Tradisional, 2019)
Background: Premature infants have a risk of death in the first year of life mainly due to prematurity. Developmental stimulation interventions in premature infants can have a positive impact on weight gain and infant development. The purpose of this study was to determine the effect of the application of growth and development intervention booklets on mothers who had a premature baby to increase the growth and development of infants aged 0-6 months in Karanganyar Regency. Method: The method used in this study is the method in this study. This research uses a quantitative method with a Quasy experiment in the form of a pre-post test design. The sample in this study was Mother and Baby in Karanganyar District who had met the inclusion and exclusion criteria. Results: The results of this study showed that there were differences in body weight and height growth before and after the study in the control group (ρ <0.05). There were no differences in development before and after the study in the control group (ρ> 0.05). There were differences in body weight and height growth before and after the study in the intervention group (ρ <0.05). There are differences in development before and after the study in the control group (ρ <0.05). There is no effect of the application of growth intervention booklet stimulation, but there is a developmental influence on premature infants aged 0-6 months in Karanganyar Regency. Conclusion: SDIDTK booklet can significantly improve the development of premature babies. It is expected that parents can provide stimulation to premature babies well to increase growth and development